2008
DOI: 10.1021/bc700435a
|View full text |Cite
|
Sign up to set email alerts
|

Hemozymes Peroxidase Activity Of Artificial Hemoproteins Constructed From the Streptomyces lividans Xylanase A and Iron(III)-Carboxy-Substituted Porphyrins

Abstract: To develop artificial hemoproteins that could lead to new selective oxidation biocatalysts, a strategy based on the insertion of various iron-porphyrin cofactors into Xylanase A (Xln10A) was chosen. This protein has a globally positive charge and a wide enough active site to accommodate metalloporphyrins that possess negatively charged substituents such as microperoxidase 8 (MP8), iron(III)-tetra-alpha4-ortho-carboxyphenylporphyrin (Fe(ToCPP)), and iron(III)-tetra-para-carboxyphenylporphyrin (Fe(TpCPP)). Coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 59 publications
4
57
0
Order By: Relevance
“…A double reciprocal plot of the residual fluorescence intensity at 340 nm as a function of the 1-Mn final concentration allowed calculation of a K D value of 1.5 µM for 1-Mn-Xln10A and determined that only one ligand was bound per protein [18]. This K D value was similar to that already reported for the Fe(TpCPP)-Xln10A complex (K D = 0.5 µM) [21], and was in agreement with the fact that the binding of the porphyrin cofactor occurred thanks to interactions of three of its carboxylate substituents with amino-acid side chains of the protein and that no amino-acid side chain was interacting with the metal cation. This could be explained after molecular modeling calculations [18].…”
Section: Catalysissupporting
confidence: 82%
See 2 more Smart Citations
“…A double reciprocal plot of the residual fluorescence intensity at 340 nm as a function of the 1-Mn final concentration allowed calculation of a K D value of 1.5 µM for 1-Mn-Xln10A and determined that only one ligand was bound per protein [18]. This K D value was similar to that already reported for the Fe(TpCPP)-Xln10A complex (K D = 0.5 µM) [21], and was in agreement with the fact that the binding of the porphyrin cofactor occurred thanks to interactions of three of its carboxylate substituents with amino-acid side chains of the protein and that no amino-acid side chain was interacting with the metal cation. This could be explained after molecular modeling calculations [18].…”
Section: Catalysissupporting
confidence: 82%
“…After lyophylization, 1-Mn was obtained in a quantitative yield and characterized by ESI-MS and UV-vis spectroscopy, in agreement with those already reported [18] and with an Mn(TpCPP) structure (Figure 1). To prepare the 1-Mn-Xln10A artificial hemoprotein, xylanase 10A (Xln10A) was first purified from the supernatant of S. lividans culture as reported earlier [21]. Solutions of the artificial hemoprotein were then prepared by incubating Xln10A in 50 mM sodium phosphate buffer, pH 7.0 with various amounts of 1-Mn for 30 min.…”
Section: Preparation Of the Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, new artificial peroxidases have been created by association of Fe III -meso-tetrakis(p-carboxyphenyl)porphyrin-Fe-(TpCPP)-with xylanase 10A from Streptomyces lividans (Xln10A), a glycoside hydrolase that hydrolyses b-1,4 bonds in the main chain of xylan and is available at low cost and in large quantities. [25] Two further arguments also led us to choose xylanase A. Firstly, it was recently found that a synthetic iron(II) porphyrin could be incorporated into recombinant Thermotoga maritima xylanase B, producing a heat-resistant artificial haemoprotein that, like haemoglobin and myoglobin, can bind and release dioxygen in aqueous solution. [26] Secondly, the catalytic site of xylanase 10A globally appears as a crevice that is rich in positively charged amino acids capable of incorporating anionic porphyrins such as Fe(TpCPP).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was shown that the Fe(TpCPP)-Xln10A complex no longer retained any glycosidic activity, which constituted an additional strong argument that the Fe(TpCPP) molecule was competitively incorporated into the substrate binding cleft of the (b/a) 8 TIM barrel and affected the enzymatic activity of the host xylanase. The protein thus produces steric hindrance around one of the faces of the Fe(TpCPP), [25] which constitutes an essential factor for inducing selectivity into the reactions catalysed by the porphyrin. The Xln10A-Fe-(TpCPP) artificial metalloprotein possessed a good peroxidase activity and was able to catalyse the oxidation of sulfides into sulfoxides by H 2 O 2 with high yields (up to 83 %) and with enantiomeric excesses of up to 40 %.…”
Section: Introductionmentioning
confidence: 99%